Screenwriting from the soul letters to an aspiring screenwriter - Krevolin, Richard W. 1964- (Los Angeles, California Renaissance Books, 1998)
How often have you gone to the movies and come out of the theater thinking, "I could have written that!" Many of us believe we have what it takes to turn out a Hollywood blockbuster, if only we had the right tools to help us do it. Screenwriting from the Soul is that tool. It simplifies the process, and at the same time acknowledges that writing, especially screenwriting requires a great deal of patience, stamina, and faith.

There are many books on the art of screenwriting, but none approaches the subject from the unique perspective of a dialogue between expert and novice. Screenwriting from the Soul is geared to instruct the user in the practicalities, discipline, and emotional resources required to produce that winning screenplay.

Written with wit and style in the form of an ongoing series of letters between a highly experienced, successful, but tired professor and a screenwriting novice, Screenwriting from the Soul is a heartfelt exploration of the screenwriting world that will become a mainstay of writing program curriculums across the world. It goes far beyond the textbook market to appeal to anyone who has ever wanted to write, or understand Hollywood and the creative process.

This master guide helps the reader to:
-gain new insights and knowledge about screenwriting and the filmmaking industry
-gain the necessary skills, techniques, discipline, and mindset to produce successful screenplays
-touch upon the crucial spiritual aspects of the craft
Filmography: pages 245-250.
Includes bibliographical references (pages 251-252) and index (pages 253-254).
A gift of Prof. Jovenal Velasco.
Keywords: Motion picture authorship; Television authorship